Drawing Shape Using The Demonstration Method At Nurul Islam Indonesia SMP School, Medan City - Ananda, Tiara; Azis, Adek Cerah Kurnia; SND, Raden Burhan; Yumielda, Vivi Destri (Institut Seni Indonesia Padang Panjang, 2024)
This research was motivated by the difficulties of class VIII-1 students at Nurul Islam Indonesia Middle School in making shading gradations when learning to draw shapes. Previously, 45% of students reached KKM and 55% did not. The main cause is the use of the lecture method and the lack of direction given by the teacher. This causes a lack of students interest in learning to draw shapes. The objectives of this research are 1) to determine the application of the demonstration method to the process of drawing cylindrical shapes using the black and white shading technique for class VIII students at SMP Nurul Islam Indonesia, 2) to improve the learning outcomes of 8th grade students in cylindrical drawing lessons at Nurul Islam Indonesia Middle School, Medan City. The method used is Classroom Action Research (PTK) in two cycles, each consisting of one meeting. The research results showed an increase in student interest from 81%, in cycle I to 100% in cycle II. Student learning outcomes increased from 54% (12 students) in cycle I to 77% (17 students) in cycle II. Thus the demonstration method has been shown to increase students’ interest and learning outcomes in drawing cylindrical shapes.